# How do you solve #(x-2)/6=(x-2)/(x-1)#?

ans : x = 2 and x=7

You carry out multiplication by cross.

that is,

additional simplification

transferring all data to the left side;

reduce to brackets

(x-2) (x - 7)

thus the answers are:

x = 2 and x = 7

:)

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x-2)/6=(x-2)/(x-1), we can start by multiplying both sides of the equation by 6(x-1) to eliminate the denominators. This gives us (x-2)(x-1) = 6(x-2). Expanding and simplifying, we get x^2 - 3x + 2 = 6x - 12. Rearranging the terms, we have x^2 - 9x + 14 = 0. Factoring or using the quadratic formula, we find that x = 7 or x = 2. However, we need to check if these solutions satisfy the original equation. Substituting x = 7, we get (7-2)/6 = (7-2)/(7-1), which simplifies to 1 = 1, so it is a valid solution. Substituting x = 2, we get (2-2)/6 = (2-2)/(2-1), which simplifies to 0 = 0, so it is also a valid solution. Therefore, the solutions to the equation are x = 7 and x = 2.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you divide #(-3x^3-23x^2-4x+1)/(x-4) #?
- If y varies inversely as the square of x and y=5 when x=2.5, what is the value of Y when X=9?
- How do you solve #5x+10=45#?
- If y varies inversely as x, and y = 3 as x = -2, how do you find y for the x-value of -1?
- How do you find the excluded value and simplify # (3x^2-5x-28)/(x^2+3x-28)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7